ASAI BAKTERI POTENSIAL PROBIOTIK DARI IKAN GURAMI (Osphronemus gouramy Lac) DALAM MENGHAMBAT PERTUMBUHAN Aeromonas hydrophila (Assay of Potential Probiotic Bacteria from Gurami (Osphronemus gouramy Lac) in Inhibition Growth of Aeromonas hydrophila) - Ernawati Butar Butar; Dwi Suryanto; Maragunung Dalimunthe; Ied Hidayani Parinduri (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The bacteria in fish can be found on the surface of body and the digestivetract. Some bacteria in digestive tract contribute to feed digestion by producesenzymes. Probiotics have been used to influences feed digestion and to inhibitionpotential pathogenic bacteria in fish. In this study, isolation of potential probioticbacteria from gourami stomach and intestine and assay of potential probiotic toinhibition Aeromonas hydrophila has been conducted. Bacteria isolation wasconducted using Tryptic Soy Agar (TSA) Media. Starch Agar (SA) and SkimMilk Agar (SMA) media to hydrolyze starch and casein tests. The result showed17 isolates hydrolyzed starch and casein. In addition, the isolates indicated toinhibit A. hydrophila. Morphological and biochemical tests showed 4 isolate ofpotential probiotic bacteria in the stomach and intestine of gourami (Osphronemusgouramy), were Bacillus cereus, Bacillus firmus, Bacillus coagulans, andMicrococcus sp.. B.cereus was more potential and dominate in the stomach andintestines.Keywords: A. hydrophila, B. cereus, B. firmus, B. coagulans, Micrococcus sp.,O. gouramy, Potential Probiotic.